2015
DOI: 10.1002/lary.25818
|View full text |Cite
|
Sign up to set email alerts
|

Voice characteristics associated with polycystic ovary syndrome

Abstract: 3b. Laryngoscope, 126:2067-2072, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 28 publications
0
27
0
2
Order By: Relevance
“…In another study, Aydin et al ( 27 ) examined vocal characteristics in women with PCOS and compared them to healthy matched individuals. The authors assessed the patient’s voice complaints using various scales, including VHI-10, as well as the acoustic parameters.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study, Aydin et al ( 27 ) examined vocal characteristics in women with PCOS and compared them to healthy matched individuals. The authors assessed the patient’s voice complaints using various scales, including VHI-10, as well as the acoustic parameters.…”
Section: Resultsmentioning
confidence: 99%
“…Another important difference between the studies mentioned above is the phase of the menstrual cycle in which the patients were examined. For instance, only in the study by Aydin et al ( 27 ), the women were examined in the follicular phase, which in the context of voice changes during the menstrual cycle ( 1 , 10 , 11 ) can pose a problem for comparing the described results with conclusions from other studies. The important problem can be the lack of information concerning androgens concentration in study groups of some research, as it was for example in a study carried out by Hannoun et al ( 25 ), in which the testosterone concentrations were evaluated only in some participants.…”
Section: Discussionmentioning
confidence: 99%
“…Aydin et al (9) observed abnormal muscle tension patterns and impaired vocal fold vibration based on stroboscopic findings in women with PCOS. Stroboscopy and VKG differ in terms of the type of camera apparatus used as well as the amount of pixel data that is collected.…”
Section: Discussionmentioning
confidence: 99%
“…The subtle variations in the vocal fold vibration are yet to be undiscovered. Aydin et al (9) observed abnormal muscle tension patterns with impaired vocal fold vibration in women with PCOS using videostroboscopy…”
Section: Introductionmentioning
confidence: 99%
“…Однако даже при отсутствии жалоб и объективных акустических различий при фиброскопии и стробоскопии было отмечено более частое выявление бессимптомной гипертонусной дисфонии, неполного закрытия голосовой щели и нарушения вибрации голосовых складок в группе пациентов с СПЯ по сравнению с контрольной группой. Данное явление может быть связано с повышенным уровнем андрогенов или тревожными и депрессивными расстройствами, риск которых ассоциирован с СПЯ [22].…”
Section: Introductionunclassified